A New Scheme for Fault Detection and Classification Applied to DC Motor - Laércio I. Santos; Reinaldo M. Palhares; Marcos F. S. V. D'Angelo; João B. Mendes; Renê R. Veloso; Petr Y. Ekel (Trends in Computational and Applied Mathematics, 2018)
This study presents an approach for fault detection and classification in a DC drive system. The fault is detected by a classical Luenberger observer. After the fault detection, the fault classification is started. The fault classification, the main contribution of this paper, is based on a representation which combines the Subctrative Clustering algorithm with an adaptation of Particle Swarm Clustering.